Marketing claims, promotional strategies, and product information on Malaysian e-cigarette retailer websites-a content analysis - Sameeha Misriya Shroff; Chandrashekhar T Sreeramareddy (BMC, 2024)
Abstract Background Marketing and sales of e-cigarettes are unregulated in Malaysia. We analyzed content displayed on e-cigarette retailer websites to identify marketing claims, promotional strategies, and product details in the year 2022. Methods We analyzed 30 Malaysia-based retailer websites using a mixed methods approach. Data were extracted as the frequency of occurrences of marketing claims, presence of regulatory information, product types, and flavors of e-juice as per a predefined codebook based on published literature. We also extracted textual details published on the websites about marketing claims, and slogans. Results Most retailer websites provided contact information and physical store addresses (83%) but only half had 'click through' age verification (57%) that seldom needed any identification proof for age (3%). Marketing claims were related to health (47%), smoking cessation (37%), and modernity/trend (37%) and none had health warnings. Promotional strategies were discounts (80%). starter kits (57%) and email subscriptions (53%). Product types displayed were rechargeable (97%) and disposable (87%) devices and e-liquids (90%) of an array of flavors (> 100). Nicotine presence, its concentration, and "nicotine is an addictive chemical" were displayed in 93%, 53%, and 23% of websites respectively. Conclusion Surveillance of content displayed online on e-cigarette retailer websites and regulation of online marketing and sales should be implemented by the Ministry of Health, Malaysia. Such measures are needed to prevent access to, and initiation of e-cigarette use among the youth and adults who do not smoke.